Effectiveness of Kinesio Taping and Proper Body Mechanics on Low Back Pain in Pregnancy - Fenina Virny Suryansyah; Nur Elly; Kheli Fitria Annuril (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Low back pain (LBP) It is a frequent issue affecting the musculoskeletal system experienced by pregnant women, particularly during the third trimester. Physiological and biomechanical changes during pregnancy, including hormonal alterations, increased body weight, and shifts in the center of gravity, may contribute to the development of LBP. Non-pharmacological interventions such as Kinesio Taping (KT) and Proper Body Mechanics (PBM) have been widely used as safe approaches for pain management during pregnancy. Objective: This study aimed to evaluate the impact of Kinesio Taping, Proper Body Mechanics, and their combination on pain intensity among pregnant women with low back pain. Method: This study utilized a quasi-experimental design, employing a pre-test and post-test control group method. The sample consisted of 60 pregnant women in their third trimester with low back pain were assigned to three groups: KT (n=20), PBM (n=20), and a combination of KT and PBM (n=20). The KT intervention was administered according to a standardized application procedure, while PBM consisted of education and guided practice on proper posture and movement techniques during daily activities. Interventions were implemented over seven consecutive days. The Numeric Rating Scale (NRS) was employed to evaluate pain levels prior to the intervention and again on the eighth day post-treatment. Data analysis was conducted via one-way ANOVA, supplemented by Tukey’s post hoc test for multiple comparisons Result: Following the intervention, pain scores were lower in all groups; however, the group receiving the combined treatment showed the lowest average pain intensity (mean = 3.35) followed by the Kinesio Taping group (mean = 2.15) and the Proper Body Mechanics group (mean = 1.20). One-way ANOVA demonstrated a statistically significant difference among the intervention groups (F = 16.927; p < 0.001). Post Hoc Tukey analysis further confirmed significant differences between the intervention groups Conclusion: The combination of Kinesio Taping and Proper Body Mechanics was more effective at reducing low back pain among pregnant women than either intervention alone. This intervention may be considered a safe non-pharmacological option for managing LBP during pregnancy